O etil-2-cianoacrilato como selante em coto cecal de Rattus norvegicus albinus submetidos a ressecção parcial - Faion, Adilson Gomes (2009)
Among the devices studied as alternative processes to the means commonly used in the coaptation of surgical wounds, the use of synthetic adhesives has been described and used since the 1950s. They include several cyanoacrylate-based formulations (such as ethyl-2-cyanoacrylate), since they have positive characteristics, such as a being easy to apply, quick polymerization and low toxicity, among others, and are, therefore, an often mentioned compound. Objective: To evaluate the use of ethyl-2-cyanoacrylate in treating a segmental resection in the cecum, that is partially diverted in the rat anatomy. Methods: Forty-five male Wistar rates were used, divided into three equal groups. The groups were called: Group 1: resection treated applying ethyl-2-cyanoacrylate; Group 2: suturing and applying ethyl-2- cyanoacrylate; Group 3: pouch-type suture. The animals were followed postoperatively, and half of each group was necropsied on the 14th day and the rest on the 28th day postoperatively. Thus, they were submitted to macroscopic evaluation, and fragments of cecum were collected for histological evaluation, and statistical analysis was performed. Results: The postexperiment weight gain was different in the groups (p=0.028). The presence of microabscesses was greater on the 28th day PO in group 2, compared to group 3 (p=0.0034). Collagen deposition on the 28th day PO was greater in group 1 (p=0,0368) and intensity of inflammation on the 14th day PO was greater in group 1 (p=0.0454). No statistical difference was found in the other parameters evaluated. Conclusion: Ethyl-2-cyanoacrylate was effective in the treatment proposed, and is thus an alternative to the currently used methods.